LEGAL REGULATION OF ECONOMIC ACTIVITIES UNDER THE CONDITIONS OF MARITAL STATE: EXPERIENCE AND CHALLENGES - Khomiachenko, Svitlana; Dzhura, Vladislava (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
The purpose: on the basis of the analysis of the novelties of the Ukrainian legislation regarding the legal regulation of economic activity in the conditions of martial law, identify the shortcomings and problems of such regulation and propose vectors for its improvement. Research methods: general scientific (dialectical, analysis, synthesis, statistical) and special research methods (formal-legal, logical-legal) were used. Results: the main legislative changes in the field of economic activity are outlined and analyzed. Legislative initiatives and measures of state bodies and the President of Ukraine aimed at regulating and improving the activities of business entities during martial law are revealed. The problems that hinder the development of entrepreneurial activity during the period of full-scale war have been identified. Proposals were made for their legal solution. Discussion: peculiarities of economic activity in the conditions of martial law; powers of the Council on business support; measures to support critically important enterprises; risks of business entities that provide services for the organization and conduct of gambling; expansion of economic activities for military units of the Armed Forces; simplification of defense procurement procedures; negative factors for the development of entrepreneurship and legal ways to eliminate them; continuation of the moratorium on the bankruptcy of state mines and operators of the electricity distribution system; introduction of new provisions to the Code of Ukraine on bankruptcy procedures, which prevent the bankruptcy of critical infrastructure operators.